Character Education TPACK Skills to Emergency Remote Learning During The Covid-19 Pandemic - Widyaningrum, Agnes; Yovita Mumpuni Hartarini (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The transition of education to an online environment due to the COVID-19 pandemic presents new challenges for teachers and students. On the other hand, there is only a little research on developing PCK related to character education. Pedagogical Content Knowledge (TPACK) technology solves today's online learning problems. This research aims to analyze Character Education TPACK skills for emergency distance learning during the COVID-19 pandemic. This research is a mixed methods research with a quantitative approach and is supported qualitatively. The population and sample are 200 teachers. The data collection method uses a questionnaire. The research instrument was a questionnaire consisting of 33 statements and 5 open questions, which were distributed. Data were examined numerically and subjectively using component analysis and teacher explanatory descriptions. Data analysis techniques use quantitative statistics. The research results show that the mastery of TPACK Character Education in online classes uses different learning media and instructional platforms. This research implies that in the future, teachers can increase the use of teaching materials, media, methods and learning models for appropriate subjects and follow TPACK integrated with character education to create an active, fun and meaningful learning atmosphere.